Quality Management in Improving Competitiveness in the Digital Era at Madrasa - Maulidin, Syarif; kurniawan, wakib; Rohman, Miftahur; Nawawi, M. Latif; Andrianto, Dedi (Journal of Advanced Islamic Educational Management, 2024)
In the rapidly evolving digital era, MTs 1 Lampung Tengah faces significant challenges in enhancing its competitiveness amid increasingly tight competition. One of the primary issues is how the institution can effectively manage educational quality to meet the demands of the digital age. This study aims to analyze the implementation of madrasah quality management in efforts to improve institutional competitiveness in the digital era. The research employs a descriptive qualitative approach with data collection through in-depth interviews, observations, and document analysis. The primary respondents include the head of the madrasah, teachers, and administrative staff involved in quality management. The findings indicate that the implementation of quality management at MTs 1 Lampung Tengah encompasses several key aspects, such as enhancing the competencies of teaching staff through information and communication technology (ICT) training, utilizing an integrated information management system, and applying stringent assessment standards. This quality management implementation has proven effective in improving educational quality, as reflected in the increased student achievements and parent satisfaction with educational services. Additionally, the quality management practices allow the madrasah to be more responsive to technological changes and the dynamic demands of the education market. The implications of this study suggest that quality management in madrasahs, which focuses on enhancing digital skills and technology adaptation, plays a crucial role in boosting institutional competitiveness. As a result, MTs 1 Lampung Tengah is able to compete with other educational institutions and remain relevant in the digital era. The study recommends continuous development in quality management and the enhancement of technological infrastructure to support more effective learning processes.